Terapia por fotobiomodulação em pontos de acupuntura associada ao exercício físico: implicações no tratamento de osteoartrite de joelho - (:unkn) unknown (Universidade Brasil, 2021)
Knee osteoarthritis (OA) is one of the most common progressive degenerative joint diseases worldwide and also a major cause of disability and damage to quality of life. Photobiomodulation therapy (PBMT) through low-level laser, isolated or in association with physical exercise has shown to be a promising treatment and with good results for several chronic diseases, including changes that affect the articular system. The aim of this study was to evaluate the effects of laser PBMT applied to acupuncture points associated with a resistance exercise protocol on the level of pain in women with OA. 23 volunteers were randomized into 2 groups: Control group (Ex): volunteers were submitted to a resistance exercise protocol; Photobiomodulation Group (ExP): volunteers were submitted to a resistance exercise protocol associated with PBMT applied in acupuncture points. The interventions were performed twice a week for a period of 6 weeks, totaling 12 sessions. The exercise program consisted of warming up, muscle strengthening (hip and knee flexors and extensors, hip adductors and adductors) and stretching of the main muscle groups of the lower limbs (lower limbs). PBMT (808 nm, 100 mW, 4 J in) was applied to 5 acupuncture points of the affected knee right after each exercise session. For assessment and reassessment, the numerical rating scale for pain (NRS) was applied; functionality and quality of life questionnaires (Western Ontario and MacMaster Universities Osteoarthritis Index [WOMAC]); functionality (Lequesne); physical performance tests (Timed Up and Go [TUG], Short Physical Performance Battery [SPPB]), lower limb strength and endurance (30-second sit-up test). The results show that both Ex and ExP showed a lower rate of pain, higher scores in the tests of strength and endurance, in functionality, in physical performance, mobility and balance and in WOMAC to its initial rates when compared to the final ones. However, no difference was observed between the experimental groups. Thus, it can be concluded that both PBMT in specific acupuncture points in association with physical exercise, as well as applied exercise in isolated way, show analgesic effects and have positive effects on physical capacity and quality of life in patients with OA.
Keywords: Osteoartrite de joelho; Fototerapia; Dor; Capacidade física; Engenharia Biomédica (Bioengenharia)